2018
DOI: 10.1534/g3.118.200079
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy To Isolate Modifiers ofCaenorhabditis elegansLethal Mutations: Investigating the Endoderm Specifying Ability of the Intestinal Differentiation GATA Factor ELT-2

Abstract: The ELT-2 GATA factor normally functions in differentiation of the C. elegans endoderm, downstream of endoderm specification. We have previously shown that, if ELT-2 is expressed sufficiently early, it is also able to specify the endoderm and to replace all other members of the core GATA-factor transcriptional cascade (END-1, END-3, ELT-7). However, such rescue requires multiple copies (and presumably overexpression) of the end-1p::elt-2 cDNA transgene; a single copy of the transgene does not rescue. We have m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…Other weaker regulatory inputs into gut specification have been found that result from more global effects on embryonic gene expression. These include the Sp1 orthologue SPTF-3, the histone deacetylase HDA-1, the p300-like factor CBP-1, the Pur-alpha orthologue PLP-1, the endopeptidase TASP-1, the Prion-like-(Q/N-rich)-domain-bearing protein PQN-82, and other factors that can modulate gene expression epigenetically [ 39 , 40 , 41 , 42 , 43 ]. Finally, other factors have been identified that are important for restricting the activity of SKN-1 to MS and E, such as the RNA-binding proteins MEX-1 and PIE-1 [ 44 , 45 , 46 ].…”
Section: Elucidation Of the Gut Specification Network: Maternal Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other weaker regulatory inputs into gut specification have been found that result from more global effects on embryonic gene expression. These include the Sp1 orthologue SPTF-3, the histone deacetylase HDA-1, the p300-like factor CBP-1, the Pur-alpha orthologue PLP-1, the endopeptidase TASP-1, the Prion-like-(Q/N-rich)-domain-bearing protein PQN-82, and other factors that can modulate gene expression epigenetically [ 39 , 40 , 41 , 42 , 43 ]. Finally, other factors have been identified that are important for restricting the activity of SKN-1 to MS and E, such as the RNA-binding proteins MEX-1 and PIE-1 [ 44 , 45 , 46 ].…”
Section: Elucidation Of the Gut Specification Network: Maternal Factorsmentioning
confidence: 99%
“…This ability is not a widespread property of GATA factors, as overexpression of ELT-1 and ELT-3A, two hypodermis-specific factors, does not promote gut fate [50,[65][66][67]. Interestingly, all of end-1, end-3, and elt-7 can be replaced with a single multicopy transgene that fuses the end-1 promoter to the coding region of either elt-2 or elt-7 [42,59,65].…”
Section: Elucidation Of the Gut Specification Network: Zygotic Factorsmentioning
confidence: 99%
“…In E, Wnt signaling further represses tbx-35 expression (Broitman- Maduro et al, 2006). studies revealed many novel regulators implied in endoderm development and embryogenesis (Witze et al, 2009;Du et al, 2014;Sullivan-Brown et al, 2016;Tintori et al, 2016;Dineen et al, 2018;Wiesenfahrt et al, 2018). The elucidation of C. elegans endoderm GRN provides a strong foundation from which to explore the diversification of endoderm GRN in other organisms.…”
Section: The C Elegans Endoderm Gene Regulatory Networkmentioning
confidence: 99%
“…reduced embryonic lethality which allows strain propagation despite the presence of the original lethal variant ( Geister et al . 2018 ; Wiesenfahrt et al . 2018 ; Jean et al .…”
Section: Introductionmentioning
confidence: 99%